A universal and wide-range cytosine base editor via domain-inlaid and fidelity-optimized CRISPR-FrCas9 - Lan Hu; Jing Han; Hao-Da Wang; Zhou-Hua Cheng; Chang-Ce Lv; Dong-Feng Liu; Han-Qing Yu (Nature Communications)
Abstract CRISPR-based base editor (BE) offer diverse editing options for genetic engineering of microorganisms, but its application is limited by protospacer adjacent motif (PAM) sequences, context preference, editing window, and off-target effects. Here, a series of iteratively improved cytosine base editors (CBEs) are constructed using the FrCas9 nickase (FrCas9n) with the unique PAM palindromic structure (NNTA) to alleviate these challenges. The deaminase domain-inlaid FrCas9n exhibits an editing range covering 38 nucleotides upstream and downstream of the palindromic PAM, without context preference, which is 6.3 times larger than that of traditional CBEs. Additionally, lower off-target editing is achieved when incorporating high-fidelity mutations at R61A and Q964A in FrCas9n, while maintaining high editing efficiency. The final CBE, HF-ID824-evoCDA-FrCas9n demonstrates broad applicability across different microbes such as Escherichia coli MG1655, Shewanella oneidensis MR-1, and Pseudomonas aeruginosa PAO1. Collectively, this tool offers robust gene editing for facilitating mechanistic studies, functional exploration, and protein evolution in microbes.